Glomerulonephritis in AKI: From Pathogenesis to Therapeutic Intervention - Pesce, Francesco; Stea, Emma D.; Rossini, Michele; Fiorentino, Marco; Piancone, Fausta; Infante, Barbara; Stallone, Giovanni; Castellano, Giuseppe; Gesualdo, Loreto (Frontiers in Medicine, 2021)
Acute kidney injury (AKI) is a global emergency. Sepsis, major surgery and nephrotoxic drugs are the main causes of AKI in hospitalized patients. However, glomerulonephritis accounts for about 10% of AKI episodes in adults, mainly related to rapidly progressive glomerulonephritis resulting from granulomatous polyangiitis (GPA, Wegener granulomatosis), microscopic polyangiitis (MPA), anti–glomerular basement membrane (GBM) disease: furthermore, diffuse proliferative lupus nephritis, immunoglobulin A nephropathy, post-streptococcal glomerulonephritis, mixed cryoglobulinemia, mesangiocapillary glomerulonephritis, membranous nephropathy, hemolytic uremic syndrome, thrombotic thrombocytopenic purpura and sclerodermia can induce acute renal failure. Early diagnosis of AKI due to glomerulonephritis is crucial for prompt and adequate management to improve short- and long-term outcomes. Kidney biopsy is the gold standard for the diagnosis of glomerular disease but it is not frequently performed in critically ill patients because of their critical clinical conditions. In this setting, a growing number of diagnostic assays can support the working hypothesis, including antineutrophil cytoplasmic antibodies (ANCA), anti–double-stranded DNA antibodies, anti–GBM antibodies, antistreptolysin O and anti–DNase B antibodies, cryoglobulins, antiphospholipid antibodies and complement levels. Therapeutic strategies in AKI patients with glomerulonephritis include high-dose corticosteroids, cyclophosphamide and plasma exchange. This article reviews the wide spectrum of glomerulopathies associated with AKI, describing the immunological mechanisms underlying glomerular diseases and an overview of the therapeutic options.